Meningkatkan Kemampuan Berbicara Bahasa Inggris dengan Penerapan Video Pembelajaran Siswa Kelas IX SMPN 171 Tahun Ajaran 2022/2023 - Sujiyati Sujiyati (Publikasi Indonesia, 2023)
Learning English is not only reading and writing, but also speaking. In general, students do not know how to start and what to talk about. In addition, speaking is a time-consuming process, starting from choosing a subject or topic of conversation, analyzing and classifying the science behind it, choosing the right words to express their ideas, and pouring them into a series of words. Students are also less motivated to practice speaking English. This fact resulted in students' speaking scores still below KKM (Minimum Completeness Criteria). To reduce the obstacles above, a way is needed by applying learning videos in learning English speaking skills. This research was conducted to improve English speaking skills by applying learning videos to grade IX students of SMPN 171 Jakarta, which in the end is expected to increase student achievement. This research was conducted in three cycles in three stages, namely pre-production, production process and post-production. The pre-production stage begins with curriculum review by identifying basic competencies that will be used as learning material, making the necessary instruments, looking for related references, preparing the equipment needed, selecting and training students as models. At the stage of the production process, namely carrying out the creation of learning videos sequentially according to the learning video scenario that has been made before. In the post-product stage, the learning video is ready for publication, which includes, video publication in the form of files. The results of the study can be seen from the increasing confidence of students so that students become active in speaking, the sense of responsibility and cooperation is getting better. These positive attitudes helped improve the speaking ability of grade IX students of SMPN 171 with a significant average increase from 75.9 in cycle one to 78.9 and 81.9 in cycles two and three. Learning completeness also increased from 75.8% in cycle one to 87.9% and 93.9% in cycles two and three. Thus, it can be concluded that the use of learning videos can improve English speaking skills in grade IX students of SMPN 171 Jakarta for the 2018/2019 academic year.